Hyperlipoproteinemia(a) as a dangerous genetically determined violation of lipid metabolism and a risk factor for atherothrombosis and cardiovascular diseases - O. I. Afanasieva; S. N. Pokrovsky (Российский кардиологический журнал, 2019)
Lipoprotein(a) (Lp(a)) is a complex supramolecular complex belonging to apoB100 lipoproteins. Lp(a) consists of a particle of similar low-density lipoprotein, in which the apolipoprotein molecule В100 is covalently linked by a disulfide bond with a unique polymorphic apolipoprotein(a) molecule. The concentration of Lp(a) is genetically controlled and varies over a very wide range. An elevated level of Lp(a) is an independent risk factor for atherosclerosis of the coronary, carotid and peripheral arteries, coronary artery disease and aortic stenosis, concomitant cardiovascular complications, and complications after myocardial revascularization. Despite this, the level of Lp(a) is still not taken into account in the stratification of the risk of cardiovascular diseases. In part, this may be due to the fact that neither modern drug therapy, nor new generations of biological lipid-lowering drugs have virtually no effect on the concentration of Lp(a), with the exception of a 20-30% decrease in Lp(a) by nicotinic acid and inhibitors of proprotein convertase subtilisin/kexin type 9 (PCSK9). The lecture covers the modern understanding of Lp(a) as a risk factor for cardiovascular diseases, the possibility and feasibility of its definition, and is also devoted to the modern possibilities of correcting hyperlipoproteinemia(a).